Performance and feasibility analysis of electricity price based control models for thermal storages in households. (July 2017) - Rosin, Argo; Link, Siim; Lehtla, Madis; Martins, João; Drovtar, Imre; Roasto, Indrek
Highlights: Control models could reduce energy costs, but not power consumption, or vice versa. The savings depends on a customer, market and control model behaviour. Pre-heating/cooling reduce the impact of unexpected changes in the electricity price. Combination of linear and non-linear models gives the best results. Comfort coefficients should adjusted to a real situation. Abstract: Electricity price based control models for thermal storages to balance fluctuations of price have become increasingly important. A number of previous studies in the field of demand side management deal with price based load control to balance the power grid. However, inadequate attention has been paid to comfort and profitability issues of end users. Therefore, insufficient solutions towards profitability and comfort issues may be a serious barrier to demand response. The aim of our paper is to analyse the performance and feasibility of electricity price based control models for thermal storages in households taking into account aspects of comfort. We simulated and compared existing control models and our models. The influence of different models and volatility of the real-time electricity price on the energy cost and electricity consumption of studied loads (i.e. water heater, freezer) have been estimated. While the cost and electricity reduction calculations do not take into account comfort issues, a performance calculation methodology has been developed. The performance is ensured when by minimized temperature change, as compared to maximum comfort settings, the cost reduction/electricity saving is maximized. The control models showing the best performance (incl. electricity or cost savings) under different comfort situations are described.